Sexual Selection May Not Often Reduce Gene Flow Between Locally Adapted Populations. A Review of Some Evidence, and Suggestions for Better Tests - Edelaar, Pim (Frontiers in Ecology and Evolution, 2022)
Sexually-selected traits are often dependent on an individual’s physical condition, or otherwise indirectly reflect the ecological performance of individuals. When individuals disperse between populations that are locally adapted to different environments, their ecological performance may decline. This in turn may result in more poorly expressed sexual traits, and thereforeultimately in a lower reproductive success. Hence, sexual selection may reduce the effective gene flow between populations, and thereby maintain or even enhance population divergence. This hypothesis was developed in Van Doorn et al. (2009) and published in a highly visible journal (Van Doorn et al. 2009, Science). Here I review the subsequently published empirical tests of this hypothesis. I downloaded all metadata (incl. abstracts) of papers citing Van Doorn et al., and read those papers that undertook relevant tests. To my surprise, only very few papers provided explicit tests of the hypothesis, this never involved plants, and only one study found support for it. While sexual selection may therefore not often reduce gene flow between locally adapted populations, some improvements to experimental design and choice of study system are noted. I therefore also provide a detailed list of suggestions for high quality tests of this hypothesis. This hopefully acts as a catalyst for more and better studies to test whether sexual and natural selection can work in synergy to reduce effective dispersal, and thereby protect and promote adaptive population divergence.